TEST OF LEAF EXTRACT OF Toona sureni AND Beauveria bassina FUNGI TO BAGWORM MORTALITIES OF Paraserianthes falcataria - Endah Suhaendah; Aditya Hani; Benyamin Dendang (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2007)
Cultivation of albizia as high priority of community forest of West Java in large scale have turned into monoculture stand. These stand has become vulnerable to insect attack such as bagworm. Attack of bagworm took place in the dry season causing growth retardation which in some cases leads to tree death. The aim of this research is to examine the affect of leaf extract of Toona sureni and extract of Beauveria bassiana fungi to kill bagworm and also compare level effectively with organofosfat synthetic insecticides. The result showed that at 7 day after application, highest mortality of bagworm were found on trees treated with T. sureni leaf extract (100%) followed by B. bassiana (92,31%) and organofosfat synthetic insecticides (76,15%).